Produksi Fitoaleksin pada Tusam (Pinus merkusii Jungh. et de Vriese) sebagai Respon Infeksi Fungi Mikorisa - S. Widyaningsih; S. M. Widyastuti; Sumardi Sumardi (Universitas Atma Jaya Yogyakarta, 2006)
The experiment aimed to detect (1) mycorrhizal infection induced phytoalexins production of the root of tusam and (2) its activity in suppressing a dumping off fungi, Fusarium sp and Rhizoctonia solani. Production of phytoalexins was detected from the extracts of mycorrhizal root of old trees and 4, 6 and 8 week-old seedlings in alcohol using a UV-spectrophotometer. The antifungal activity of phytoalexins was studied by inoculating the pathogenic fungi into mycorrhizal seedlings of tusam. The results showed that the spectra of phytoalexins of extracted mycorrhizal and non-mycorrhizal roots ranged from 203.2 to 204.6 nm. Higher antifungal concentrations of antifungal compound was obtained from the root extracts of old trees and 4 week-old seedlings, indicated by the higher spectrophotometric absorbance (0.315 and 0.324 g-1 root ml-1 ethanol), compared to that extracted from non-mycorrhizal root of the same plant origin. Mycorrhizal roots significantly suppressed the development of Fusarium sp. and Rhizoctonia solani.